Apparently your classroom lecture and your textbook omitted a very important point: namely, the Zero Product Property! :shock:marshall1432 said:10x'squared' - 13x =3
marshall1432 said:Solve by factoring and applying the zero product property.
10x'2squared' - 13x=3
WORK DONE :
10x'squared' - 13x =3
(10x-9)(x-4)=3 <-- How did you get here from above
If you multiply out (10x - 9)(x - 4),
do you get 10x^2 - 13x?
10x^2 - 49x + 36 totally different from 10x^2 - 13x
10x-9=3 = 10x=12 ; x-4=3 = x=7
Go to the sites suggested by stapel - you'll find many problems worked out step-by-step.marshall1432 said:I am so lost subhotosh khan. Can you help me with this step by step so I can figure this thing out? Thanks